2005
DOI: 10.1210/me.2004-0359
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor 1-C2 Is Regulated by Prolactin and Shows a Distinct Expression Pattern in the Mouse Mammary Epithelial Cells during Development

Abstract: We have previously demonstrated that the transcription factor nuclear factor (NF)1-C2 plays an important role in the mammary gland for the activation of the tumor suppressor gene p53. It also activates the milk genes carboxyl ester lipase and whey acidic protein, implying that NF1-C2 participates both in the establishment of a functional gland and in protection of the gland against tumorigenesis during proliferation. In this study, we have developed a new sensitive NF1-C2-specific antiserum for immunohistochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…Previously we have reported that prolactin is involved in maintaining the basal levels of NF1-C2 proteins in the nuclei of mammary epithelial cells in pregnant mice as well as in cells derived from a virgin mouse (15). To investigate the hypothesis that prolactin prevents NF1-C2 degradation, we incubated the double-thymidine-blocked cells with prolactin for 4 h. Western blot analysis of extracts from these cells revealed that prolactin indeed prevents degradation of NF1-C2 (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously we have reported that prolactin is involved in maintaining the basal levels of NF1-C2 proteins in the nuclei of mammary epithelial cells in pregnant mice as well as in cells derived from a virgin mouse (15). To investigate the hypothesis that prolactin prevents NF1-C2 degradation, we incubated the double-thymidine-blocked cells with prolactin for 4 h. Western blot analysis of extracts from these cells revealed that prolactin indeed prevents degradation of NF1-C2 (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Further, using studies with mouse mammary epithelial NMuMG cells and mammary tissue from heterozygous prolactin receptor knockout mice as a basis, we have demonstrated that the prolactin signaling pathway has a role in the maintenance of the NF1-C2 protein in mammary epithelial nuclei. Since treatment with prolactin resulted in a net increase of NF1-C2 protein in the whole cell and not simply in a nuclear translocation of already present cytoplasmic proteins, we suggested that prolactin regulates NF1-C2 by a mechanism distinct from its regulation of Stat5 (15).…”
mentioning
confidence: 81%
“…Tissue microarrays were incubated with the affinity purified rabbit polyclonal pNF1-C2 antiserum (1:1,000 dilution) according to the protocol described in ref. 9.…”
Section: Methodsmentioning
confidence: 99%
“…Studies using mammary epithelial cells and tissue from heterozygous prolactin receptor knockout mice showed that prolactin is required for maintenance of the transcription factor nuclear factor 1-C2 (NF1-C2) in the mammary epithelium (9). The NF1 family consists of four genes (NF1-A, NF1-B, NF1-C, and NF1-X), each producing different splice variants, thereby generating a large number of protein isoforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation